Meningkatkan Literasi Siswa Sekolah Dasar Melalui Peningkatan Kompetensi Guru Dalam Menggunakan Media Pembelajaran Berupa Majalah Anak - Khairat Umami; M. Witra Kusuma (Indonesian Journal of Multidisciplinary Scientific Studies, 2024)
The purpose of this research is to determine the role of teachers in increasing competence in using learning media in the form of children's magazines to increase student literacy. The method in this research is descriptive qualitative. The data sources used in this research are primary data obtained from interviews with MI Halwani school teachers and secondary data obtained from documentation, namely documents in the form of journals and books related to the research theme. The result of this research is that the Mini KKG was carried out to improve the ability of MI Halwani teachers in developing literacy-based learning media. This is important in order to increase teacher professionalism in carrying out learning in the classroom. At MI Halwani school the teachers use children's magazines as learning media. Children's magazines in learning can function as a tool to build literacy in elementary school students. The use of pictures in children's magazines can be of particular interest to elementary school students. Children's magazines can hypnotize students because they contain figures who are usually idolized. Apart from that, story lines in children's magazines can also develop students' imagination and foster critical attitudes.